Bearing Ring Creep: Wear Prediction and Remedy in an EV Power Transmission System - Xiaobo Zhou; Lijun Cao; Victor Brizmer; Thijs Nijdam; Andreas Vierling; Po Shen; Amy Chen; Dave Rybski; Daniel Jansen (Tribology Online)
Lighter weight and higher power density are major trends in electric vehicles (EV). To realize these market needs, speed and torque in electric motors increases continuously and light Al alloy housings are commonly used as the bearing seat in the power transmission system. To ease mounting, there is a loose fit between the bearing outer rings (OR) and the housing. Ring creep, i.e. a slow unidirectional movement of the bearing OR may occur. This ring creeping in combination with a high load may cause significant wear on the softer housing. The wear may result in mis-alignment and damage of the bearings and gears. In this study, it is shown that abrasive wear is the dominant wear mechanism during ring creep in EV power transmission system tests. To simulate the ring creep wear, a creep wear model based on the creep by strain mechanism was developed with the SKF BEAST software. Input data for the coefficient of friction and the wear coefficient were obtained from an in-house developed Ring-on-Ring test setup. The model was verified with a power transmission system test, showing good agreement between simulated and measured wear depth. Finally, remedies are proposed to minimize the ring creep wear.